Investigating insulin’s role in regulating local aromatase in growth plate development - Sicui Hu; MinMin Xue; Yao Dong; Cheng Li; Lingyan Qiao; Rongxiu Zheng (PLoS ONE, 2025)
Introduction Obesity-associated hyperinsulinemia is hypothesized to disrupt linear growth trajectories, though the mechanisms remain unclear. This study investigates these mechanisms using a high-fat diet-induced rat model. Methods Twelve healthy 1-week-old Sprague-Dawley rats (60–80 g) were randomized into two groups: a control group fed a standard diet and an obese group fed a high-fat diet. After 6 weeks of dietary intervention, weekly body weight and naso-anal length were recorded. At the end of the study, all rats were euthanized, and blood samples were collected for further analysis. Serum biochemical parameters, including insulin levels, were measured by ELISA. Tibiae and humeri were harvested for bone length measurement. Growth plates were isolated for histological analysis, immunohistochemistry, radioimmunoassay, PCR, and Western blotting. Results Higher serum insulin levels were observed in the obese group than in the control group (36.46 ± 1.69 mU/L, vs 22.96 ± 1.99 mU/L, p < 0.01). The obese group showed higher growth plate length (426.63 ± 6.28 μm, vs 331.13 ± 28.93 μm, p < 0.01), especially in proliferative and hypertrophic areas than the control group. Immunohistochemistry analysis revealed positive staining for brownish-yellow granules in these regions. Higher aromatase levels and insulin receptor (IR) expression were observed in the growth plates, primarily in the hypertrophic region. Immunohistochemical staining indicated that aromatase expression was primarily localized to the hypertrophic zone in obese rats.Moreover, the aromatase activity in the obese group was significantly higher than that in the control group (47.29 ± 0.87 U, vs 41.12 ± 1.50 U,p ＜ 0.01). The relative mRNA expression of CYP19A1 and insulin receptors (IR) in the growth plates of obese rats was significantly higher than that in the control group (0.0039 ± 0.0026-, vs 0.0001 ± 0.00025, p < 0.01 and 0.15- ± 0.07, vs 0.03 ± 0.02, p < 0.01). Western blot analysis revealed higher expression of CYP19A1 and IR in the growth plates of obese rats (1.81 ± 0.12-, vs 1.02 ± 0.04-, p < 0.01 and 2.05 ± 0.34, vs 1.04 ± 0.13-, p < 0.01). Conclusion In this study, we found a significant increase in the expression of insulin receptors, indicating that insulin signaling regulates aromatase expression, thereby affecting epiphyseal growth plate development. However, the molecular mechanisms by which insulin receptors regulate aromatase expression remain unclear.